1986
DOI: 10.1288/00005537-198609000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Silent otitis media: Clinical applications

Abstract: Silent (masked) otitis media refers to usually chronic pathological conditions behind an intact tympanic membrane which may be clinically “undetected” or “undetectable.” Correlations are described for pathological changes in temporal bones and clinical considerations for 1. silent otitis media associated with Hemophilus influenzae meningitis in infants, 2. silent otitis media — the continuum, 3. silent otitis media — sequelae, and 4. chronic silent otitis media.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0
3

Year Published

1988
1988
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 9 publications
1
20
0
3
Order By: Relevance
“…Histological sections of gerbil temporal bones and bullae are easier to prepare for histopathology studies, and the gerbil's middle ear ultrastructure, cell types, and cell-type distribution support its use as an animal model for human OM (Chole and Chiu, 1985). It is also worth noting that the course of the disease and its sequelae are quite similar in gerbils to those described by Friedman (1955aFriedman ( ,b, 1956Friedman ( ,1957 and Paparella et al (1980) for humans.While inherent dangers exist in making anatomical and physiological comparisons across species, we do believe that the distinctive biology of some individual species (e.g., the rat's small, underventilated MEC and horizontal ET) lends itself to a higher disease incidence. Conversely, we feel that the hypertrophied, well-ventilated and -drained MECs of the gerbil and chinchilla are related to their respective nonsusceptibility to OM (see Fig.…”
supporting
confidence: 72%
“…Histological sections of gerbil temporal bones and bullae are easier to prepare for histopathology studies, and the gerbil's middle ear ultrastructure, cell types, and cell-type distribution support its use as an animal model for human OM (Chole and Chiu, 1985). It is also worth noting that the course of the disease and its sequelae are quite similar in gerbils to those described by Friedman (1955aFriedman ( ,b, 1956Friedman ( ,1957 and Paparella et al (1980) for humans.While inherent dangers exist in making anatomical and physiological comparisons across species, we do believe that the distinctive biology of some individual species (e.g., the rat's small, underventilated MEC and horizontal ET) lends itself to a higher disease incidence. Conversely, we feel that the hypertrophied, well-ventilated and -drained MECs of the gerbil and chinchilla are related to their respective nonsusceptibility to OM (see Fig.…”
supporting
confidence: 72%
“…This was supported by the studies of Dumich et al 10 , which states that size of tympanic membrane perforation have an adverse effect on bone conduction threshold. These results can be explained on the basis of work of Paparella et al 4 , on the role of round window in the development of SNHL in CSOM.…”
Section: Percentagementioning
confidence: 62%
“…In a study by Kaur et al 3 , the incidence of SNHL was found to be 13.64% when the duration of disease was <5 years and progressively close to 33.33% when the duration of disease was > 26 years. Paparella et al 4 , have also noted increasing duration of the disease in their studies. However in studies by Levine et al 6 , no consistent relationship was found between the amount of relative SNHL and symptoms duration.…”
Section: Percentagementioning
confidence: 82%
See 1 more Smart Citation
“…Paparella et al [9] studied 111 infant ears; 54 of these showed histological evidence of otitis media. Of these, 20 cases presented with clinical manifestations, while 34 did not and were identified as silent otitis media.…”
mentioning
confidence: 99%